Athens Demapped. Archaeology, Heritage, and Urban Transformation (Coimbra University Press, 2025)
Athens Demapped. Archaeology, Heritage, and Urban Transformation explores the entangled relationships between classical heritage, memory, and modernity in the evolving city of Athens. Dimitris Plantzos interrogates how archaeology, tourism, and urban planning have shaped the city's identity, revealing Athens not as a timeless monument to antiquity but as a contested landscape where past and present collide. Rather than a neutral cultural asset, Athens’ classical legacy has been mapped, commodified, and weaponised – used both to forge collective memory and to marginalise dissenting voices. Plantzos critically engages with nostalgia, gentrification, and the politics of heritage, exposing how the myth of Athens as the “cradle of Western civilisation” continues to serve shifting ideological and economic agendas. At the heart of the book is the concept of “demapping”: the erasure or overwriting of certain spaces, histories, and communities to reinforce dominant narratives and commercial interests. Drawing on archaeological insight, urban theory, and cultural critique, Athens Demapped reimagines the city as a site of overlapping histories and contested futures. At a moment of rapid urban transformation, this book offers a vital perspective on the uses of the past and the right to the city. Essential reading for scholars of heritage, politics, and space.